Technology Entrepreneurship (ENT600) Be space / Faruq Ahmad Kendong ... [et al.] - Ahmad Kendong, Faruq; Muthuraman, Aifa; Salim, Siti Nur Aiman; Mat Zaib, Muhammad Muazam; Wan Mohd Saipallah, Wan Muhammad Afiq (2018)
Be Space LCD Curtain Display is a curtain that combines the function of a curtain and a television screen, or LCD screen. It aims to reduce the space taken up by a television set and using the space on the curtain, making it more convenient for households as this product allows the users to change the views while doubling as a LCD screen for viewing pleasures. The television set and curtains have always had a place in our homes; however, space now is becoming scarcer as prices are increasing. The team hopes to tackle this by combining the. two, allowing more space in a home to be freed up and making use of the surface of a curtain as a display. Since visual media plays an important role in our daily lives, the Be Space LCD Curtain Display approaches those two problems.